Forecasting Cash Flows from Investment - Szpulak, Aleksandra (Prognozowanie przepływów pieniężnych z inwestycji, 2010)
The aim of this article was to prove hypothesis stating that the type of investment is the main factor that influences the organization of the forecasting process and character of produced cash flow forecasts. In fact the forecasting process and forecast itself arc different when we consider different types of investment projects, which was described in detail in this paper.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 91, s. 166-176
Keywords: forecasting; cash flows from investment